The study of the level of spatial comfort of housing at Seri Iskandar, Perak / Nurul Solehah Zolkifle - Zolkifle, Nurul Solehah (2014)
The study of the level of the spatial comfort of housing at Seri Iskandar is conducted by the objective of, to identify the spatial comfort level of housing design in Seri Iskandar based on the study and a reading from the journal and also from the information got from my advisor. I also referring to the government portal for strong information and some book related to the study. This study is take placed at Seri Iskandar, Perak. Near to Universiti Teknologi Mara (uitm) Seri Iskandar, Perak. It is also placed minutes from Ipoh and an hour to Lumut. The most housing that are at Seri Iskandar is a terrace housing, so that my research will be focused to the terrace housing only. I carried out this study by doing some reading an observation and also a measurement are take placed.